Risk Assessment in the Maritime Industry - Mousavi, M.; Ghazi, I.; Omaraee, B. (Engineering, Technology & Applied Science Research, 2017)
Risk assessment is a well-developed field which many operators are currently applying to improve their operations and reduce their risk exposure. This paper is intended to provide an overview of the risk assessment for mariners in the Maritime transportation. The risks addressed are primarily those affecting the safety of a vessel, facility or operation. The concept of risk is defined, and the methods available to assess the risks associated with an operation are described. Regulatory requirements that have prompted the development of modern risk assessment practices are described, and future regulatory trends are discussed. There are many different analysis techniques and models that have been developed to aid in conducting risk assessments. A key to any successful risk analysis is choosing the right method (or combination of methods) for the situation at hand. This is achieved through critical analysis of the available data concerning marine crises. This paper provides a brief introduction to some of the analysis methods available and suggests risk analysis approaches to support different types of decision making within the maritime transportation to cope with crises. Finally, as awareness of risk assessment increases, the benefits which can be realized through its application will continue to increase. Organizations in both the public and the private sector are becoming more and more familiar with the benefits associated with risk-based approaches to managing safety and consequently reducing crisis in maritime transportation.